A Systematic Literature Review of Talent Management And Knowledge Management In Improving Higher Education Performance - Ramaditya, Muhammad; Maarif , Mohamad Syamsul; Affandi , M. Joko; Sukmawati, Anggraini (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
Purpose – This paper seeks to reveals talent management as a distinctive organizational strategy mechanism that affects knowledge management, university transformation, and the intellectual environment in high-performance education Methodology/approach – There were 753 articles total since only those that were ready for publishing and were written in English were chosen. A search of some of these publications with the keywords